The Jacobson Radical of the Endomorphism Semiring of P.Q.- Principal Injective Semimodules - Aljebory et al. (مجلة بغداد للعلوم, 2020)
In this work, we introduced the Jacobson radical (shortly Rad (Ș)) of the endomorphism semiring Ș =  ( ), provided that  is principal P.Q.- injective semimodule and some related concepts, we studied some properties and added conditions that we needed. The most prominent result is obtained in section three